The Relationship Between Self-Care By Parents Based On Nursing Assessment According To Dorothea Orem With The Incidence Of Diarrhea In Children Under Five Years Old In The Working Area Of Landono Health Center South Konawe District - Sri Wahyuni; Faridah Moh Said; Nisha Nambiar (Fakultas Kesehatan IKesT Muhammadiyah Palembang, 2023)
Data from Community Health Center Landono shows that the number of diarrhea cases in under fives shows increase and tends to be higher by 2016 by 44.7%, by 2017 by 46.3% and by 2018 from January to April by 43.4%. The purpose of the study to determine the relationship of self-care by parents of theoretical review Dorothea Orem Universal Self Care, Development Self Care and Health Deviation Self Care with Diarrhea Occurrence in ToddlersThis research method is quantitative with Case Control design. Population of all mothers with children under five in the Working Area of Puskesmas Landono of South Konawe Regency, April 2018 period, amounting to 161 people. Samples were taken using Simple Random Sampling technique amounted to 62. Analysis of Chi-Square test, Odds Ratio and contingency coefficient.The results of the study were strongly correlated between the Universal Self Care assessment and Diarrhea Evaluation in Infants under x2count> X2table (13,547> 3,841); p <α (0,000 <0.05); = 0.4674 OR = 10,688 CI 95% (2,987-38,237), there is a strong correlation between Development Self Care assessment with Diarrhea occurrence in Toddler 10,185> 3,841; p <α (0,000 <0,05 ); = 0.4861; OR = 10,185 CI 95% (3,126-33,188) and there is a strong correlation between Health Deviation Self Care with Diarrhea Evaluation in Toddler 16,585> 3,841; p <α (0,000 <0,05); = 0.5172; OR = 11.979 CI 95% lower limit-upper limit (3,606- 39,791).Conclusion the better the self-care needs assessment conducted by the mother tends to her child does not suffer from diarrhea.Suggestions for health workers need to be socialized through counseling about prevention of diarrhea through nursing assessment on underfives suffering from diarrhea.